Bimatoprost in the treatment of eyelash hypotrichosis - Simon K Law (Dove Medical Press, 2010)
Simon K LawJules Stein Eye Institute, University of California, Los Angeles, California, USAAbstract: Eyelashes hypotrichosis is a condition indicated by an inadequate amount of eyelashes. Hypertrichosis of eyelashes, characterized by excessive eyelash growth, is a regular phenomenon associated with ophthalmic prostaglandin and prostamide analogs. Recently, the US Food and Drug Administration approved Latisse® (bimatoprost 0.03% solution), identical to the ophthalmic solution for glaucoma treatment, for increasing eyelash length, thickness and darkness in patients with hypotrichosis of the eyelashes. When prostaglandin and prostamide analogs interact with the prostanoid receptors in the hair follicle, this most likely stimulates the resting follicles (telogen phase) to growing follicles (anagen phase). Prostaglandin and prostamide analogs may also prolong the anagen phase of eyelashes, leading to an increase of eyelash length. Although bimatoprost is effective in promoting increased growth of healthy eyelashes and adnexal hairs, its effectiveness in patients with eyelash alopecia areata is debatable and its protective effect is not yet studied in patients with eyelash loss secondary to radiation or chemotherapy. Bimatoprost is generally safe when applied to the base of the eyelashes at the lid margin with minimum side effects. However, other ocular or systemic side effects associated with ophthalmic prostaglandin and prostamide analogs may occur when instilled on the surface of the eye, and patients must be informed and monitored.Keywords: bimatoprost, Latisse, prostaglandin, prostamide, eyelash, hypotrichosis